2014
DOI: 10.1542/peds.2012-2650
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Early DMSA Scan for VUR in Young Children With Febrile UTI

Abstract: WHAT'S KNOWN ON THIS SUBJECT:The sensitivities of 99m Tcdimercaptosuccinic acid in predicting vesicoureteral reflux reported by different institutions were at different levels for young children with acute febrile urinary tract infection. Tc-dimercaptosuccinic acid (DMSA) scan in predicting dilating vesicoureteral reflux (VUR) among young children with a febrile urinary tract infection (UTI). WHAT THIS STUDY ADDS: METHODS:The medical records of children (#2 years of age), presenting with febrile UTI between Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…Among 151 patients with dilating VUR, 149 (98.7%) had abnormal acute-phase renal scans yielding a sensitivity of 96.15% and a positive predictive value (PPV) of 34%. Overall, 46 patients (8.8%) had scars on delayed DMSA scans [14]. It can be gleaned from these studies and some others that DMSA can be used as an effective screening tool to identify patients who are likely to have dilating VUR and UTI recurrence.…”
Section: The Top-down Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 151 patients with dilating VUR, 149 (98.7%) had abnormal acute-phase renal scans yielding a sensitivity of 96.15% and a positive predictive value (PPV) of 34%. Overall, 46 patients (8.8%) had scars on delayed DMSA scans [14]. It can be gleaned from these studies and some others that DMSA can be used as an effective screening tool to identify patients who are likely to have dilating VUR and UTI recurrence.…”
Section: The Top-down Approachmentioning
confidence: 99%
“…Although TDA could detect clinically-significant VUR with a sensitivity of 85%–96% [13142122], the low specificity and modest PPV of TDA does not justify the prohibitive cost and the unnecessary ionizing radiation exposure to all children after febrile UTIs should the TDA be universally adopted. Bearing in mind that 85% of children with symptomatic or febrile UTI will never experience UTI recurrence [23], only 15% would benefit from further testing and possible treatment.…”
Section: The Top-down Approachmentioning
confidence: 99%
“…The majority will have a normal scan and among these few will present a recurrence. The strength of this study is to have linked abnormal DSMA with risk of recurrent UTI as most previous studies have focused on the relationship between results of various diagnostic tests and the presence or absence of VUR or probability of resolution of VUR [6][7][8][9][10][11][12][13][14][15][16].…”
mentioning
confidence: 99%
“…The acquisition of renal scarring through the association of reflux, urinary infection, and intrarenal reflux has been observed clinically and experimentally. 19,20 Nuclear scintigraphy can detect areas of acute renal inflammation and chronic scarring, and this capability has changed imaging of pediatric UTIs. In our study, DMSA findings showed that 23.5% of the children (33 0f 140) had renal scarring.…”
mentioning
confidence: 99%